2020
DOI: 10.1186/s12981-020-00317-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of first-line antiretroviral therapy failure among adults and adolescents living with HIV/AIDS in a large prevention and treatment program in Nigeria

Abstract: Background A substantial number of persons living with HIV (PLWH) in Nigeria do not experience durable viral suppression on first-line antiretroviral therapy (ART). Understanding risk factors for first-line treatment failure informs patient monitoring practices and distribution of limited resources for second-line regimens. We determined predictors of immunologic and virologic failures in a large ART delivery program in Abuja, Nigeria. Methods A retrospective cohort study was conducted at the University of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Patients on rst-line ART were more likely to experience viral load suppression. This result is consistent with other authors' observations that the rst-line regimen should be initiated in all HIV-positive people starting treatment (14,19,20). As argued by some authors for the change from the former to the latter (21).…”
Section: Discussionsupporting
confidence: 92%
“…Patients on rst-line ART were more likely to experience viral load suppression. This result is consistent with other authors' observations that the rst-line regimen should be initiated in all HIV-positive people starting treatment (14,19,20). As argued by some authors for the change from the former to the latter (21).…”
Section: Discussionsupporting
confidence: 92%
“…For example, an analysis from the same study site found that one-fifth of Sanger sequences from 198 people who had failed first-line ART had no detectable drug resistance mutations. 37 This may reflect complete non-adherence or very poor adherence, in which case a switch to second-line ART would not be common practice. On the other hand, other studies have shown that extensive resistance does occur when people remain on failing NNRTI-based regimens long term.…”
Section: Discussionmentioning
confidence: 99%
“…This mirrors the results from previous first-line ART studies from sub-Saharan Africa that have shown clinical and immunologic failure to be poor predictors of viral failure during first-line ART. 10,[17][18][19] Viral failure was identified less often than one might expect from other second-line studies, [20][21][22][23][24][25] particularly when considering the long follow-up period of this analysis. However, the low frequency of viral load measurements, which was only done in 55% of participants, meant that this is likely to be an underestimate of the true proportion of the cohort that had viral failure.…”
Section: Discussionmentioning
confidence: 93%
“…This mirrors the results from previous first-line ART studies from sub-Saharan Africa that have shown clinical and immunologic failure to be poor predictors of viral failure during first-line ART. 10,17–19…”
Section: Discussionmentioning
confidence: 99%